Waste Management Training through Composting: A Creative Solution for the Community of Sinduadi Village, Sleman - Suryani, Erma Aris; Alghiffari, Eka Kevin; Siswanto, Deny Hadi (The Indonesian Institute of Science and Technology Research, 2025)
This activity aims to provide education on waste and its potential dangers, while also conducting training on how to process household organic waste into compost. The activity was held in Sendangadi Village, Mlati, with 40 participants. It was a workshop where a speaker delivered a specific topic, followed by a discussion based on the presentation. In this training, participants were asked to bring organic waste, such as leftover green vegetables and fruit scraps from their household kitchens, to be used as materials for composting. The activity emphasized the importance of active community involvement in waste management, community-based composting methods, and the economic potential of compost as an alternative business opportunity. As a result of the activity, the community gained valuable knowledge about waste management. Additionally, the feedback was overwhelmingly positive from both village officials and participating residents. The participants demonstrated high enthusiasm and interest in applying the knowledge gained, particularly in practicing composting at home using organic waste as raw material a practical solution to reduce waste in their environment.